2015
DOI: 10.1158/1535-7163.mct-15-0279
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine Kinase 2 Inhibitor ABC294640 Reduces the Growth of Prostate Cancer Cells and Results in Accumulation of Dihydroceramides In Vitro and In Vivo

Abstract: Despite recent advances in the development of novel therapies against castration resistant prostate cancer, the advanced form of the disease remains a major treatment challenge. Aberrant sphingolipid signaling through sphingosine kinases and their product sphingosine-1-phosphate can promote proliferation, drug resistance, angiogenesis and inflammation. The sphingosine kinase 2 inhibitor ABC294640 is undergoing clinical testing in cancer patients, and in this study we investigated the effects this first-in-clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 43 publications
(67 reference statements)
5
94
0
Order By: Relevance
“…Indeed, we have shown that proteasomal degradation of SphK1 by 'indirect' inducers occurs via additional inhibition of dihydroceramide desaturase (Degs1) (an enzyme within the de novo ceramide synthesis pathway). In this regard, SKi inhibited Degs1 activity in Jurkat and prostate cancer cells [44,45]. We have proposed that Degs1 might function to limit protein degradation flux through the proteasome [44] and therefore its inhibition by SKi promotes proteasomal degradation of SphK1.…”
Section: Hypertension?mentioning
confidence: 98%
“…Indeed, we have shown that proteasomal degradation of SphK1 by 'indirect' inducers occurs via additional inhibition of dihydroceramide desaturase (Degs1) (an enzyme within the de novo ceramide synthesis pathway). In this regard, SKi inhibited Degs1 activity in Jurkat and prostate cancer cells [44,45]. We have proposed that Degs1 might function to limit protein degradation flux through the proteasome [44] and therefore its inhibition by SKi promotes proteasomal degradation of SphK1.…”
Section: Hypertension?mentioning
confidence: 98%
“…It was recently found that ABC294640 acts as a weak estrogen receptor (ERα) antagonist with low micromolar affinity (100-fold higher than estrogen and 200-fold higher than tamoxifen) [113]. However, the recent discovery that ABC294640 inhibits Des1, leading to a 3-fold increase in dihydroceramide species [53,80] means that earlier studies using this inhibitor may need some re-interpretation.…”
Section: Abc294640mentioning
confidence: 99%
“…More recent studies with ABC294640 have implied roles for SK2 in regulating autophagy [119], transcription of key cancer-promoting genes such as c-Myc [36,98] and pro-inflammatory mediators through NF-κB [120][121][122][123]. ABC294640 also induced proteasomal degradation of SK1 and Des1 [80], Myc and other targets such as androgen receptor [53,98] and Mcl-1 [37] through an as yet undetermined mechanism that appears to be related to its ability to inhibit Des1 [80].…”
Section: Abc294640mentioning
confidence: 99%
See 1 more Smart Citation
“…This might represent an early event in ER stress via deployment of News ER-associated degradation (ERAD) that is then switched to CHOP/caspase-3-induced apoptosis in the presence of bortezomib. Second, ABC294640 also inhibits dihydroceramide desaturase (Des1) [6,7] that we have suggested might be a 'gate-keeper' of the proteasome [6]. Third, we have also shown that the dual SK1/SK2 and Des1 inhibitor, SKi (4-([4-(4-chlorophenyl)thiazol-2-yl] amino) phenol) induces an ER stress/UPR in T-cell lymphoblastic leukemic (T-ALL) cells that results in a protective cell survival autophagy [8].…”
mentioning
confidence: 99%